Tempest [large type] - Jenkins, Beverly, 1951- (Center Point Large Print, 2018)
"Regan Carmichael--an independent spirit equally at home in denims and dresses--travels to Wyoming to be the mail-order bride for Dr. Colton Lee--a widower who insists he only wants someone to care for his daughter. Despite family disapproval and an unseen enemy, Colt will soon risk all to make this marriage a true union"--